Advances in the Diagnosis of Latent Tuberculosis Infection - Zhang H; Guan W; Zhou J (Infection and Drug Resistance)
Haiying Zhang,1 Weiwei Guan,2 Jikun Zhou3 1School of Public Health at Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 2Department of Tuberculosis, The Fifth Hospital of Shijiazhuang, Shijiazhuang, Hebei, People’s Republic of China; 3The Institute of Medical Research, The Fifth Hospital of Shijiazhuang, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Jikun Zhou, The Institute of Medical Research, The Fifth Hospital of Shijiazhuang, Shijiazhuang, Hebei, People’s Republic of China, Email 13933880581@163.comAbstract: Latent tuberculosis infection (LTBI) is a critical stage of tuberculosis infection in which Mycobacterium tuberculosis (MTB) is dormant and does not cause active disease. Traditionally, the most commonly used clinical methods for diagnosing LTBI have been the tuberculin skin test (TST) and the interferon-gamma release assay (IGRA). Recently, however, novel skin tests, molecular biology techniques, and cytokine biomarkers have been developed. This review summarizes the latest research on the diagnosis of LTBI, highlighting new tools and methods to improve detection and differentiation from active tuberculosis(ATB).Keywords: latent infection, tuberculosis, diagnosis, public health, review